INFEKTIFITAS Spodoptera exigua NUCLEOPOLYHEDROVIRUS (SeNPV) YANG DIPERKAYA DENGAN BAHAN PENGAKTIF TERHADAP LARVA Spodoptera exigua Huebner - Samsudin Samsudin; Teguh Santoso (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Spodoptera exigua Huebner nucleopolyhedrovirus (SeNPV) is an entomophathogenic virus of onion caterpillar S. exigua larvae commonly used as bioinsecticide. The major limitations of SeNPV for biocontrol of onion caterpillar is it requires long time for the virus to kill the insect host. This research was aimed to find out the material as phagostimulant to increase the infectivity of SeNPV and to determine the optimum boric acid concentration as an enhancer for SeNPV activities. This research was conducted at laboratory using Cipanas isolate of SeNPV and third instar of S. exigua larvae. Phagostimulant used are 5% ofsucrose, soybean sauces, molases, sugar and turmeric filtrate,and the enhancers used are 0,1%, 1%, 5% and 10% concentration of boric acid. This result indicated that soybean sauces and sucrose increased S. exigua consumption and enhanced the infectivity of SeNPV. When mixed with polyhedra of SeNPV, 1% to 5% sucrose significantly increased S. exigua consumption and increased the infectivity of SeNPV, while 10% sucrose tended to decrease the feeding of S. exigua. Boric acid enhanced the infectivity of SeNPV. However, the increase of boric acid concentration should be restricted maximum at 5% for avoiding the negative impacts on the environment.